Structural and optical characterizations of BaSnO3 nanopowder synthesized by aqueous sol-gel method - Kumar U.; Ansaree Md.J.; Upadhyay S. (My University, 2025)
Precursor gel for preparation of nanocrystalline BaSnO3 powder was synthesised by aqueous sol-gel method using Ba(OH)2 · 8 H2O and Na2SnO3 · 3 H2O as raw materials. Thermogravimetric and differential scanning calorimetric analyses of the raw materials, precursor gel and a mechanical mixture of raw materials were carried out to understand the mechanisms involved in the formation of the single phase BaSnO3. Based on the thermal analysis, the precursor gel was calcined at 400, 800 and 1400 °C for 4 h to obtain pure phase BaSnO3 powder. X-ray diffraction pattern of the powder calcined at 1400 °C was refined for atomic coordinate, lattice parameter (a = 4.1117(2) Å) and occupancies using Rietveld refinement analysis. The average crystallite size calculated from the Scherrer formula is ?35 nm. Transmission electron micrograph of the powders confirmed that particle sizes are in range of 20–40 nm. The phase purity of the powder calcined at 1400 °C was further examined by Fourier transform infrared spectroscopy. Optical properties of the BaSnO3 powder were studied by UV-visible absorption and photoluminescence (PL) spectra. The band gap energy (3.09 eV) obtained from the Tauc plot confirmed the semiconductor nature of the powder. The CIE coordinate corresponding to PL spectrum exhibited an intense emission in the visible region.